You are on page 1of 13

3rd

Grading
Product Rule for Derivatives

In Calculus and its applications we often encounter functions that are expressed as
the product of two other functions, like the following examples:
h(x)=xex=(x)(ex)
h(x)=x2sinx=(x2)(sinx)
h(x)=ex2cos2x=(ex2)(cos2x)
In each of these examples, the values of the function h can be written in the form
h(x)=f(x)g(x)
for functions f(x) and g(x). If we know the derivative of f(x) and g(x), the Product
Rule provides a formula for the derivative of h(x)=f(x)g(x):

h (x)= f(x)g(x) =f (x)g(x)+f(x)g (x)

Examples:
If h(x)=xex then
h (x) = (x) ex+x(ex)
= ex+xe^x

If h(x)=x^2sinx then
h (x) = (x^2) sinx+(x^2)(sinx)
=2xsinx+x^2cosx
Reflection:
The product rule for finding derivatives was quite easy. The concept is pretty much
understandable and easy to comprehend with. Although some exercises are hard to
answer, the lesson was quite enjoyable as well.

Quotient Rule for Derivatives

Suppose we are working with a function h(x) that is a ratio of two


functions f(x) and g(x).
How is the derivative of h(x) related to f(x), g(x), and their derivatives?
Quotient Rule

Let f and g be differentiable at x with g(x) =0. Then f g is differentiable at x and


[f(x)g(x)] =g(x)f (x)f(x)g (x)
[g(x)]^2

Examples

If f(x)=2x+1, then
x-3

f (x) = (x-3)d/dx[2x+1]-(2x-1)d/dx[x-3]
[x-3]^2
= (x-3)(2)-(2x-1)(1)
[x-3]^2
= 7__
[x-3]^2

Reflection:
Its a bit difficult compared to the product rule, but if you analyze the concept, you
will have no trouble understanding the lesson.

DIFFERENTIATION USING THE CHAIN RULE

The following problems require the use of the chain rule. The chain rule is a rule for
differentiating compositions of functions. In the following discussion and solutions

the derivative of a function h(x) will be denoted by or h'(x) . Most problems


are average. A few are somewhat challenging. The chain rule states formally that

.
However, we rarely use this formal approach when applying the chain rule to
specific problems. Instead, we invoke an intuitive approach. The chain rule tells us
to first differentiate the outer layer, leaving the inner layer unchanged (the
term f'( g(x) ) ) , then differentiate the inner layer (the term g'(x) ) . This process will
become clearer as you do the problems. In most cases, final answers are given in
the most simplified form.

Example:

= 2 (3x+1) (3)
= 6 (3x+1)
Reflection:
When we first took part in this lesson, its a bit confusing for me. But when I noticed
the pattern of the chain rule. It was then easy for me to execute this rule.

Differentiation of Exponential Functions


Formulas and examples of the derivatives of exponential functions, in calculus, are
presented. Several examples, with detailed solutions, involving products, sums and
quotients of exponential functions are examined.
But first, these are the formulas for finding the derivatives of exponential functions:
d/dx(a^u)= a^u ln a du/dx d/dx(e^u)= e^u
du/dx

Example:
Example 1: Find the derivative of f(x) = 3 x + 3x 2
Let g(x) = 3 x and h(x) = 3x 2, function f is the sum of functions g and h: f(x) =
g(x) + h(x). Use the sum rule, f '(x) = g '(x) + h '(x), to find the derivative of
function f

f '(x) = 3 x ln 3 + 6x
Example 2: Find the derivative of f(x) = e x / ( 1 + x )
Let g(x) = e x and h(x) = 1 + x, function f is the quotient of functions g and h:
f(x) = g(x) / h(x). Hence we use the quotient rule, f '(x) = [ h(x) g '(x) - g(x) h
'(x) ] / h(x) 2, to find the derivative of function f.

g '(x) = e x

h '(x) = 1

f '(x) = [ h(x) g '(x) - g(x) h '(x) ] / h(x) 2

= [ (1 + x)(e x) - (e x)(1) ] / (1 + x) 2
Multiply factors in the numerator and simplify

f '(x) = x e x / (1 + x) 2

Reflection:
To be honest, I didnt understand the lesson at first because I was already used to
Sir Sebials way of teaching. Sir Mag-usara has a different approach to teaching, but
Ive managed to keep up with this lesson by reviewing.

Derivatives of Logarithmic Functions


First, let's look at a graph of the log function with base e, that is:
f(x) = loge(x) (usually written "ln x").
The tangent at x = 2 is included on the graph.

The slope of the tangent of y =


ln x at \displaystyle{x}={2}x=2 is \displaystyle\frac{1}{{2}}21. (We can observe
this from the graph, by looking at the ratio rise/run).
If we did many more examples, we could conclude that the derivative of the
logarithm function y = ln x is
Dy/dx= 1/x
Note 1: Actually, this result comes from first principles.
Note 2: We are using logarithms with base e. If you need a reminder about log
functions, check out Log base e from before.

Here are the formulas for finding the derivatives of logarithmic function:
1) d/dx(lnu)= du/dx
u
Example:
Find the derivative of
y = ln x2
the answer is:
d/dx(lnx^2)=2x
x2

2) d/dx(log a^u)= loga e du/dx


u
Example:
Find the derivative of
y=log5(5x+2)^1/2
=log5 e 5/2(5x+2)^-1/2
(5x+2)^1/2
=log5 e 5(5x+2)^1/2
2(5x+2)^1/2
y= 5log5e
2(5x+2)
3) d/dx(log10^u)=log10 e du/dx
u
Example:
Find the derivative of
y=log10(5x+2)^1/2
=log10 e 5/2(5x+2)^-1/2
(5x+2)^1/2
=log10 e 5(5x+2)^1/2
2(5x+2)^1/2
y= 5log10e
2(5x+2)
Reflection:
I understood this lesson better compared to exponential functions. Maybe because I
started to get a hang on Sir Mag-usaras teaching style.

Derivatives of Trigonometric Functions


Trigonometric functions are useful in our practical lives in diverse areas such as
astronomy, physics, surveying, carpentry etc. How can we find the derivatives of
the trigonometric functions?
Here are the formulas to be used in finding the derivatives of trigonometric
functions:
d/dx (sin u)=cos u du/dx d/dx (cot u)= -csc^2 u du/dx
d/dx (cos u)= -sin u du/dx d/dx (sec u)= sec u tan u du/dx
d/dx (tan u)= sec^2 u du/dx d/dx (csc u)= -csc u cot u du/dx

Examples:
d/dx(sin 2x)= cos 2x d/dx(2x) d/dx(cot 5x)= -csc^2 5x d/dx(5x)
= 2cos2x = -5csc^25x
d/dx(cos 2x)= -sin 2x d/dx(2x) d/dx(sec 5x)= sec 5x tan 5x d/dx(5x)
= -2sin2x = 5sec 5x tan
5x
d/dx (tan 2x)= sec^2 2x d/dx(2x) d/dx(csc 5x)= -csc 5x cot 5x d/dx(5x)
= 2sec^22x = -5csc 5x cot 5x
Reflection:
Its a bit confusing compared to the last lessons, maybe because of the different
signs in each formula, and the insides of the formulas are nearly the same. But with
more practice given to this lesson I managed to catch up the lesson as well.

Derivatives of Inverse Trigonometric Functions


Here are the formulas for the Inverse Trigonometric Functions:
1 - Derivative of arcsin x.
The derivative of f(x) = arcsin x is given by

f '(x) = 1 / sqrt(1 - x 2) . du/dx

2 - Derivative of arccos x.
The derivative of f(x) = arccos x is given by

f '(x) = - 1 / sqrt(1 - x 2) . du/dx

3 - Derivative of arctan x.
The derivative of f(x) = arctan x is given by

f '(x) = 1 / (1 + x 2) . du/dx

4 - Derivative of arccot x.
The derivative of f(x) = arccot x is given by

f '(x) = - 1 / (1 + x 2) . du/dx

5 - Derivative of arcsec x.
The derivative of f(x) = arcsec x tan x is given by

f '(x) = 1 / (x sqrt(x 2 - 1)) . du/dx

6 - Derivative of arccsc x.
The derivative of f(x) = arccsc x is given by

f '(x) = - 1 / (x sqrt(x 2 - 1)) . du/dx

Here are some examples on some of the formulas:


Example 1: Find the derivative of f(x) = x arcsin x

Solution to Example 1:

Let h(x) = x and g(x) = arcsin x, function f is considered as the product of


functions h and g: f(x) = h(x) g(x). Hence we use the product rule, f '(x) =
h(x) g '(x) + g(x) h '(x), to differentiate function f as follows

f '(x) = x (1 / sqrt(1 - x 2)) + arcsin x * 1 = x / sqrt(1 - x 2) + arcsin x

Example 2: Find the first derivative of f(x) = arctan x + x 2

Solution to Example 2:

Let g(x) = arctan x and h(x) = x 2, function f may be considered as the sum of
functions g and h: f(x) = g(x) + h(x). Hence we use the sum rule, f '(x) = g
'(x) + h '(x), to differentiate function f as follows
f '(x) = 1 / (1 + x 2) + 2x = (2x 3 + 2x + 1) / (1 + x 2)

Reflection:
In all our lessons in 3rd Grading, I thought this lesson was the most difficult. The
process was a little bit confusing. But nevertheless, I understood the lesson well
enough to have a decent score.

Derivatives of Hyperbolic Functions


Here are the formulas for finding the derivative of hyperbolic functions:
d/dx (sin h u)= cos h u . du/dx d/dx (cot h u)= -csc^2 h u. du/dx
d/dx (cos h u)= sin h u. du/dx d/dx (sec h u)= -sec h u tan h u . du/dx
d/dx (tan h u)= sec^2 h u. du/dx d/ dx (csc h u)= -csc h u cot h u . du/dx

Here are some examples on some of the formulas:


Example 1: Find the derivative of f(x) = sinh (x 2)

Solution to Example 1:

Let u = x 2 and y = sinh u and use the chain rule to find the
derivative of the given function f as follows.
f '(x) = (dy / du) (du / dx)
dy / du = cosh u, see formula above, and du / dx = 2 x
f '(x) = 2 x cosh u = 2 x cosh (x 2)
Substitute u = x 2 in f '(x) to obtain
f '(x) = 2 x cosh (x 2)

Example 2: Find the derivative of f(x) = 2 sinh x + 4 cosh x

Solution to Example 2:

Let g(x) = 2 sinh x and h(x) = 4 cosh x, function f is the sum of functions g
and h: f(x) = g(x) + h(x). Use the sum rule, f '(x) = g '(x) + h '(x), to find the
derivative of function f

f '(x) = 2 cosh x + 4 sinh x


Example 3: Find the derivative of f(x) = cosh x / sinh (x 2)

Solution to Example 3:
Let g(x) = cosh x and h(x) = sinh x 2, function f is the quotient of functions g
and h: f(x) = g(x) / h(x). Hence we use the quotient rule, f '(x) = [ h(x) g '(x) -
g(x) h '(x) ] / h(x) 2, to find the derivative of function f.

g '(x) = sinh x

h '(x) = 2 x cosh x 2 (see example 2 above)

f '(x) = [ h(x) g '(x) - g(x) h '(x) ] / h(x) 2

= [ (sinh x 2) (sinh x) - (cosh x)(2 x cosh x 2) ] / (sinh x 2) 2

Reflection:
Since it was nearly the same as finding the derivative of trigonometric
functions, I can now easily solve problems regarding this lesson. Although the
difference in signs between trigonometric functions and hyperbolic functions, is
sometimes confusing as well.

Implicit Differentiation
- Sometime functions are given not in the form of y=f(x) but in a more
complicated form in which it is difficult or impossible to express y
explicitly in terms of x. Such functions are called implicit functions.
Example:
x^2+y^2-4x+5y-8=O
2x+ 2y dy/dx-4+5 dy/dx-0=0
2y dy/dx+5 dy/dx=-2x+4
Dy/dx (2y+5) = -2x+4
2y+5 2y+5
Dy/dx= -2x+4
2y+5
As you can see from our example above, you derive all the components existing in
the functions. But there is a twist, you leave dy/dx to the components in the
function that doesnt have the x value, since you only derive with respect to x
(except constant values) .if with respect to y, do the vice versa. After that, we
undergo the simplification of the derivatives that youve got from the function. So
we separate the ones with the dy/dx from the ones with none. Then we factor out
the dy/dx from the ones with this form. And lastly, divide both side of the with the
factored variables to find dy/dx
Reflection:
Arguably one of the easiest lessons in 3rd Grading. It was more on simple analysis of
the functions given. To be honest, It was too easy compared to the others. So I
didnt have much trouble in understanding the concept of this lesson.